Penerjemahan Mu’jam Tarjamah Berbasis Online dan Cetak: Analisis Kamus Arab Al-Ma’any dan Mahmud Yunus - Nuroh, Nuroh (UIN ANTASARI, 2025)
Dictionaries are an important tool in Arabic translation and learning. Technological developments have given rise to online-based dictionaries such as al-Ma'any, which provide ease in translating, while printed dictionaries by Mahmud Yunus still hold historical and methodological value. This study employs a qualitative method with a content analysis approach. The purpose of this study is to compare the results of translation analysis and translation quality between the online-based mu'jam al-Ma'any and the Mahmud Yunus printed dictionaries. The results of the study indicate that the quality of a good translation depends on the context and purpose of the translation itself. Consequently, mu'jam al-Ma'any has an advantage in terms of speed of access and diversity of translation results, both in linguistic aspects (grammatical, semantic, and pragmatic) as well as non-linguistic aspects (cultural, social, and situational). In contrast, Mahmud Yunus's dictionary demonstrates a higher level of accuracy and consistency, especially concerning terms that have special meanings in Islam, although the search process takes longer. Both dictionaries possess advantages that complement each other. The al-Ma'any online dictionary is suitable for quick and dynamic needs, while the Mahmud Yunus printed dictionary is more relevant for in-depth study. Combining the two can enhance the quality of Arabic translation.